Graphic design for everyone. (Dorling Kindersley Limited, 2019)
Create your own blog, logo, website, and much more. Trying to give your blog extra visual impact? Need a new look for a personal, business, or community project? With this beginner's guide to graphic design, you'll be able to do this and much more! There have never been more opportunities to promote yourself online or in print, but to succeed you need to master the art of visual communication - combining the building blocks of type, image, and colour into an appealing, accessible message. Graphic Design for Everyone is your guide right from the start of the process, showing you first how to define your brand, your message and your audience. Learn the basic principles and language of design and how to use the building blocks successfully. Find out how to create a brand plan, discover how a typeface sets the mood, and learn to use colour theory for maximum impact. Gain inspiration from real-life examples in a wide range of styles, and workshops that help you to focus on the right solutions for you. Once you've learned the basics, turn to the ten design projects to help you create your own designs. From letterheads and business stationery to a marketing brochure and online shop, each project shows you how to assemble your design toolkit and use it for stunning results. And to complete the process, there's plenty of practical advice on publishing online, dealing with printers, and commissioning professional designers. Whether you're a complete newcomer to design or keen to build on what you know, Graphic Design for Everyone is the only resource you'll ever need.